PENGARUH KUALITAS PELAYANAN DAN SERVICESCAPE TERHADAP KEPUASAN NASABAH PADA PT BANK SINARMAS KANTOR KAS RAFLESSIA CABANG BATAM - Anggraini, Rizki Amalia; Setiawan, Joko (SCIENTIA JOURNAL, 2019)
This study aims to explain the description of the variables of service quality, servicescape and customer satisfaction and to know and analyze partially and simultaneously service quality and servicescape to customer satisfaction at PT Bank Sinarmas Raflessia cash office in Batam branch. The population studied in the study was a customer of PT Bank Sinarmas, the Batam branch of Raflessia cash office with 3000 customers. The sample in this study amounted to 125 customers with probability sampling technique. This type of research is quantitative research. This study uses a multiple linear regression analysis method. Test the quality of data used in this study using validity and reliability tests which indicate that the indicators used are valid for measuring existing variables. From the results of this study conclusions are that service quality and servicescape have a positive and significant effect on customer satisfaction at the PT Bank Sinarmas Raflessia cash office in the Batam branch.